APPROXIMATION BY NONLINEAR FOURIER BASIS IN GENERALIZED HOLDER SPACES - Aslan, Hatice; Guven, Ali (Yildiz Technical Univ, 2019)
In this paper, the value of deviation of a function f from its nth generalized de la Vallee-Poussin mean V-n(alpha)(lambda, f) with respect to the nonlinear trigonometric system is estimated for the classes of 2 pi-periodic functions in the uniform norm parallel to . parallel to C(T) and in the generalized Holder norm parallel to . parallel to omega(beta) where f is an element of H-omega alpha(T) and 0 <= beta < alpha <= 1.
Keywords: Generalized de la Vallee-Poussin means; generalized Holder class; nonlinear Fourier basis